A Psychoanalytic and Psychosocial Study of Inner Conflict in Bisaraha by Abeer Nehme - Hubbillah, Muhammad Ziyad (Litteratura: Jurnal Bahasa dan Sastra, 2025)
This article analyzes the inner conflict experienced by the lyrical persona in the song “Bisaraha” by Abeer Nehme from the perspective of literary psychology. The inner conflict portrayed in the song is understood as a representation of emotional struggles rooted in past experiences and the need to be loved within an intimate relationship. This study employs a qualitative approach using content analysis as its primary method. The primary data consist of the Arabic lyrics of “Bisaraha” and their translation, while the secondary data include the official music video and relevant psychological literature. The analysis is conducted through data reduction, identification of psychological themes, and in-depth interpretation based on Karen Horney’s Social Psychoanalytic Theory and Erik Erikson’s Psychosocial Development Theory. The findings indicate that the lyrical persona experiences basic anxiety arising from painful past relational experiences. This anxiety gives rise to a conflict between two neurotic tendencies proposed by Horney: moving toward people, which reflects the need for love and protection, and moving away from people, which represents the impulse to withdraw as a form of self-protection. In addition, the phenomenon of the Tyranny of the Should significantly influences the persona’s inner conflict, as reflected in idealistic expectations that a relationship must be perfect and that a partner should be capable of healing past emotional wounds. From Erikson’s perspective, the persona is situated within the crisis of Intimacy vs. Isolation, where the desire for emotional closeness confronts fears of rejection and betrayal. This study concludes that the inner conflict depicted in “Bisaraha” represents a complex portrayal of human emotional struggle in the pursuit of healthy intimacy. The findings affirm that song lyrics can serve as a significant source for understanding the psychological dynamics of literary characters and constitute a relevant object of study within literary psychology.